Whey Protein Supplementation Effects on Body Composition, Performance, and Blood Biomarkers During Army Initial Entry Training - McAdam, Jeremy S.; Lyons, Kaitlin D.; Beck, Darren T.; Haun, Cody T.; Romero, Matthew A.; Mumford, Petey W.; Roberson, Paul A.; Young, Kaelin C.; Lohse, Keith R.; Roberts, Michael D.; Sefton, JoEllen M. (Frontiers in Nutrition, 2022)
This study assesses if a lower dose of whey protein can provide similar benefits to those shown in previous work supplementing Army Initial Entry Training (IET) Soldiers with two servings of whey protein (WP) per day. Eighty-one soldiers consumed one WP or a calorie matched carbohydrate (CHO) serving/day during IET (WP: n = 39, height = 173 ± 8 cm, body mass = 76.8 ± 12.8 kg, age = 21 ± 3 years; CHO: n = 42, 175 ± 8 cm, 77.8 ± 15.3 kg, 23 ± 4 years). Physical performance (push-ups, sit-ups, and a two-mile run) was assessed during weeks two and eight. All other measures (dietary intake, body composition, blood biomarkers) at weeks one and nine. There was a significant group difference for fat mass (p = 0.044) as WP lost 2.1 ± 2.9 kg and had a moderate effect size (Cohen's d: −0.24), whereas the CHO group lost 0.9 ± 2.5 kg and had only a small effect size (d: −0.1). There was no significant group-by-time interaction on fat-free mass (p = 0.069). WP gained 1.2 ± 2.4 (d: 0.1) and CHO gained 0.1 ± 3 (d: 0) kg of FFM on average. There was a significant group by week 1-fat free mass interaction (p = 0.003) indicating individuals with higher initial fat-free mass benefitted more from WP. There were no group differences for push-up (p = 0.514), sit-up (p = 0.429) or run (p = 0.313) performance. For all biomarkers there was a significant effect of time as testosterone (p < 0.01), testosterone to cortisol ratio (p = 0.39), and IGF-1 (p < 0.01) increased across training and cortisol (p = 0.04) and IL-6 (p < 0.01) decreased. There were no differences in groups across IET for any of the biomarkers. We conclude one WP serving is beneficial for FM and for FFM in soldiers with high baseline FFM but may not significantly alter biomarker response or physical performance of IET soldiers who have high relative dietary protein intakes.